PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI - Desi Novitasari; Deny Edy Widodo; Nani Septiana (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Firm value represents investors’ assessment of a company’s performance and future prospects, making it an important indicator in investment decision-making. This study aims to examine the effect of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and profitability on firm value with firm size as a control variable in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employs a quantitative approach using panel data regression and utilizes secondary data obtained from financial statements and annual reports. The sample was determined using a purposive sampling technique, resulting in 26 companies with a total of 78 initial observations, which were reduced to 64 after the removal of outlier data. The results indicate that partially, GCG and CSR have no significant effect on firm value, while profitability has a positive and significant effect. Firm size as a control variable does not have a significant effect; however simultaneously, all independent variables significantly affect firm value. The robustness test, conducted by replacing the profitability proxy from ROA to ROE and firm value from Tobin’s Q to PBV, shows consistent results, indicating that the model is robust.